Pengaruh Ilkilm Organisasi dan Kompetensi Pegawai terhadap Kinerja Pegawai dengan Mediasi Motivasi pada Dinas-dinas di Kabupaten Kudus - Rofiatun, -; Masluri, - (Jurnal Analisis Manajemen, 2011)
The purpose of this study were (1) to analyze and test the effect of organizational climate on employee motivation, (2) to analyze and test the effect of competence on employee motivation, (3) to analyze and test the effect of organizational climate to employee performance at the offices of District Ghost, (4) to analyze and test the effect of competence on employee performance, (5) to analyze and examine the influence of motivation to employee performance, (6) to analyze and test the effect of organizational climate to employee performance organizations through the mediation of motivation, (7) for analyze and test the effect of competence on staff performance through the mediation of motivation.The population in this study are all Civil Servants in the Office - Office in the Kudus District, amounting to 1044 people. While the sample size was set at 110 respondents with proportional random sampling technique, data collection was the questionnaire. Data analysis using a model of causality or influence, to test the hypothesis proposed in this research, technical analysis is used Structural Equation Modelling or SEM, which is operated through the AMOS program.Based on the analysis concludes that (1) there is a significant positive effect between the Organization of the motivational climate proved, because the CR value of 3.205 with P value of 0.001. (2) there is a significant positive influence of competence on motivation evident because the CR value of 2.770 with P value of 0.006. (3) there is a significant positive influence of climate on performance organization prove the value of CR of 2.291 with P value of 0022. (4) there is a significant positive effect between competency to employee performance data prove it is known that the CR value of 2.241 with P value of 0.025. (5) there is a significant positive effect of motivation on the performance of CR pegawa proved her value of 2.092 with P value of 0.036. (6) there is a significant positive influence of climate on the performance of the Organization with the mediation of motivation is not proven it can be seen that the CR value of 1.866 with P value of 0061. (7) there is a significant positive influence of competence on the performance of employees with the mediation of motivation does not prove this case the data is known that the CR value of 1.763 with P value of 0062